Exam AZ-900 : Microsoft Azure fundamentals. - Cheshire, Jim (LiveLessons (Indianapolis, Ind.), 2023)
4 Hours of Video Instruction Prepare for Microsoft Exam AZ-900--updated October 2022--and demonstrate your foundational-level knowledge of cloud services and how Microsoft Azure can provide those services. Exam AZ-900 Microsoft Azure Fundamentals (Video), Third Edition,is designed for professionals in any non-technical or technical role who want to take a first step toward expanding their understanding of cloud services and cloud-based solutions using Microsoft Azure. Through expert instruction and demos, prepare for the exam and take a step forward in your career. This video focuses on the skills measured by the exam: Describe cloud concepts Describe Azure architecture and services Describe Azure management and governance For 25 years, instructor and author Jim Cheshire has worked at Microsoft in various roles, most recently in technical readiness across the entire Azure business. Jim is a bestselling Azure author and live training instructor. In this video, Jim shares his insights and organizes coverage by exam objective to help you make the most effective use of your study and exam prep time. Skill Level Beginner Who Should Take This Course Certification candidates preparing for exam AZ-900 Microsoft Azure Fundamentals Anyone who needs to demonstrate a foundational-level understanding of cloud services and cloud-based solutions with Microsoft Azure Anyone who wants to take a first step in learning Microsoft Azure concepts and terminology Course Requirements This video assumes no prior knowledge of Azure or cloud services.